Women's entrepreneurship in Iran : role models of growth-oriented Iranian women entrepreneurs - Sarfaraz, Leyla (Springer, 2017)
This book presents the nature, challenges and successful cases of female entrepreneurship in Iran. The first part of the book provides a comprehensive insight into Iran's entrepreneurship ecosystem and its accessibility for women by exploring and analyzing data from relevant national and international sources, in particular from the Statistical Center of Iran, Global Entrepreneurship Monitor, World Bank (Doing Business, Gender Equality and Development), World Economic Forum (Global Gender Gap Report, Global Competitiveness Report), and the United Nations Development Plan. Trends in entrepreneurial perceptions and intentions, as well as developments in entrepreneurial activity in Iran from 2008 to 2013, are also studied for both genders. In order to establish a benchmark for the relative position of Iranian women in the region, the main related indices are also compared to those in Egypt, Pakistan, Saudi Arabia and Turkey. In turn, the second part of the book highlights selected role models of growth-oriented female Iranian entrepreneurs who have successfully run a variety of traditionally male-dominated businesses in Iran and internationally, despite the hostile business environment and various gender stereotypes.